2013
DOI: 10.1523/jneurosci.2804-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping the Function of TRPV1-Expressing Sensory Neurons by Targeted Axonal Silencing

Abstract: Specific somatosensations may be processed by different subsets of primary afferents. C-fibers expressing heat-sensitive TRPV1 channels are proposed, for example, to be heat but not mechanical pain detectors. To phenotype in rats the sensory function of TRPV1+ afferents, we rapidly and selectively silenced only their activity, by introducing the membrane-impermeant sodium channel blocker QX-314 into these axons via the TRPV1 channel pore. Using tandem mass spectrometry we show that upon activation with capsaic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 47 publications
5
78
0
1
Order By: Relevance
“…Based on the changes in rectification produced by internal QX-314, coapplication of 10 mM QX-314 with capsaicin for 2-6 min produced accumulation of intracellular QX-314 to typical concentrations of 50 -100 M (and up to 200 -500 M in some cells). This agrees well with previous estimates of QX-314 accumulation based on the reduction of voltage-dependent sodium current (Brenneis et al 2013). In the present experiments, the accumulation of internal QX-314 evoked by capsaicin clearly did not require pannexin channels because it was equally prominent and rapid when TRPV1 was expressed in C6 cells lacking pannexin expression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Based on the changes in rectification produced by internal QX-314, coapplication of 10 mM QX-314 with capsaicin for 2-6 min produced accumulation of intracellular QX-314 to typical concentrations of 50 -100 M (and up to 200 -500 M in some cells). This agrees well with previous estimates of QX-314 accumulation based on the reduction of voltage-dependent sodium current (Brenneis et al 2013). In the present experiments, the accumulation of internal QX-314 evoked by capsaicin clearly did not require pannexin channels because it was equally prominent and rapid when TRPV1 was expressed in C6 cells lacking pannexin expression.…”
Section: Discussionsupporting
confidence: 93%
“…Permeation and block of TRPV1 channels by the cationic lidocaine derivative QX-314. J Neurophysiol 109: 1704 -1712, 2013. First published January 9, 2013 doi:10.1152 doi:10.…”
mentioning
confidence: 99%
“…Our data show that the TRPV1 population is crucial for the development and transmission of heat hyperalgesia. This is consistent with previous findings where acute blockade of the TRPV1 population using the sodium channel blocker QX-314 [2-((2,6-dimethylphenyl)amino)-N,N,N-triethyl-2-oxoethanaminium] in combination with capsaicin attenuated the development of hyperalgesia after complete CFA injections (Brenneis et al, 2013). Moreover, desensitization of TRPV1-positive afferents using the capsaicin analog resiniferatoxin fully blocked CFA-induced thermal hypersensitivity (Okun et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…The transient receptor potential cation channel subfamily V member 1 (TRPV1), which is expressed in a heterogeneous population of primary afferent neurons (Tominaga et al, 1998), has been shown to have a central role in inflammation-induced heat hyperalgesia (Caterina et al, 2000;Davis et al, 2000;Mishra et al, 2011). The TRPV1 population is also required for the development of thermal and mechanical hyperalgesia after complete Freund's adjuvant (CFA) injections (Okun et al, 2011;Brenneis et al, 2013). However, the neurotransmission behind these processes is still under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, targeted silencing by QX-314 and capsaicin of TRPV1-positive axons abolishes thermal, mechanical, and (somewhat surprisingly) cold hyperalgesia in the rat (Brenneis et al, 2013), and perineural (Kissin and Szallasi, 2011) or epidural RTX (a molecular scalpel TRP Channels as Drug Targets that selectively abolishes TRPV1-expressing nerves) produces lasting analgesia in rats with neuropathic pain secondary to spinal nerve ligation . Importantly, intra-articular RTX injections ameliorate pain behavior and restore ambulation in dogs with severe OA pain ( Fig.…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 99%